PELATIHAN PEMBUATAN MINUMAN HERBAL UNTUK MENJAGA KESEHATAN WANITA DI MASA PRODUKTIF - Yudhi Novriansyah; Zahlimar Zahlimar; Mela Sari (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
Women have complicated bodies. Throughout their existence, they go through the anatomical, physiological, and reproductive development processes. From birth to adulthood, there occurs development, and as a woman, the body's organs develop flawlessly and entirely. In comparison to a male, a woman's body develops differently, especially in terms of the reproductive organs, genitalia, endocrine system, and skeleton. The fast-paced and practical lifestyle elements of today's metropolitan society have an impact on the food ingested, which is bad for the body's health. The majority of high-risk illnesses, including heart disease, breast cancer, cervical cancer, osteoporosis, autoimmune disease, stroke, depression, and others, affect women more than males. The Community Service Partners are the management of the Family Welfare Development Team (TP-PKK) in West Bungo Village, Bungo Regency. The majority of PKK administrators, besides their activities as housewives, also work in government, private and entrepreneurial institutions, where due to business, consumption patterns and types of food eaten are unhealthy, such as fast- food which can be bad for the health of the body. especially reproductive health. Therefore, the purpose of this activity is to provide training and skills for TP-PKK administrators in making traditional herbal drinks with raw materials from rhizome plants such as Ginger, Turmeric, Temu Lawak, Kencur, Galangal which are very useful in helping to maintain body and reproductive health. in productive Ages.